Employment the database of software (Microsoft Access) in implementing and printing official documents - Hussein Hamid Khudair, (Eximia, 2024)
As a result of higher development in the world in all its fields, the circle of requirements of that development has increased in general and in administrative work specially expanded in terms of the introduction of new administrative systems and generated a routine movement that disrupts the flow of transactions in all government institutions, this has a negative impact on the speed of completing transactions and the exertion of great effort. By employees in exchange for a small number of completed transactions compared to the large numbers of uncompleted transactions. The need for technological intervention in this field has necessitated the solution of this problem, through the use of the technological capabilities available in those institutions, which are within the reach of the institution’s employees and which do not cost anything. Financial sums, as it meets the actual need to complete administrative work in a complete and simplified manner in a very short time, and there is no need to contract with software companies that work to design a special program for the organization for very exorbitant amounts, in addition to the complexity of the programs, which requires enrolling employees in training courses on how to use it, in addition to an inventory. Update to the program by the company that designed it.